HIF1A-dependent induction of alveolar epithelial PFKFB3 dampens acute lung injury - Christine U. Vohwinkel; Nana Burns; Ethan Coit; Xiaoyi Yuan; Eszter K. Vladar; Christina Sul; Eric P. Schmidt; Peter Carmeliet; Kurt Stenmark; Eva S. Nozik; Rubin M. Tuder; Holger K. Eltzschig (JCI Insight, 2022)
Acute lung injury (ALI) is a severe form of lung inflammation causing acute respiratory distress syndrome in patients. ALI pathogenesis is closely linked to uncontrolled alveolar inflammation. We hypothesize that specific enzymes of the glycolytic pathway could function as key regulators of alveolar inflammation. Therefore, we screened isolated alveolar epithelia from mice exposed to ALI induced by injurious ventilation to assess their metabolic responses. These studies pointed us toward a selective role for isoform 3 of the 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase (PFKFB3). Pharmacologic inhibition or genetic deletion of Pfkfb3 in alveolar epithelia (Pfkfb3loxP/loxP SPC-ER-Cre+ mice) was associated with profound increases in ALI during injurious mechanical ventilation or acid instillation. Studies in genetic models linked Pfkfb3 expression and function to Hif1a. Not only did intratracheal pyruvate instillation reconstitute Pfkfb3loxP/loxP or Hif1aloxP/loxP SPC-ER-Cre+ mice, but pyruvate was also effective in ALI treatment of wild-type mice. Finally, proof-of-principle studies in human lung biopsies demonstrated increased PFKFB3 staining in injured lungs and colocalized PFKFB3 to alveolar epithelia. These studies reveal a specific role for PFKFB3 in counterbalancing alveolar inflammation and lay the groundwork for novel metabolic therapeutic approaches during ALI.